Systematic approaches and analyses on voltage uprating of 132 kV transmission lines: a case study in Malaysia - Mohd Nor, Shamsul Fahmi; Ab Kadir, Mohd Zainal Abidin; Mohd Ariffin, Azrul; Osman, Miszaina; Abd Rahman, Muhammad Syahmi; Mohd Zainuddin, Noorlina (MDPI AG, 2021)
With the ageing infrastructure and fast-growing demand faced by utilities worldwide, voltage uprating is one of the most effective solutions and strategic approaches in asset management decisions. In this study, a systematic voltage uprating method is used to propose the new voltage level, based on the existing transmission lines’ physical structure, by utilising appropriate techniques. Prior to work conducted, the existing 132 kV transmission line was first examined in terms of the clearances and the components attached, and a technical issue on the clearance under still air was found to be a significant concern, particularly on phase-to-earth arrangements. Next, the proposed techniques and processes, by increasing the insulation strength and improving air conductor clearances, were used for the individual existing 132 kV transmission tower. The proposed voltage uprating of the 132 kV transmission tower comprehensively examines phase-to-earth under normal and extreme wind conditions based on electrical clearance requirements for 275 kV transmission lines. The proposed uprating model was then simulated using the Finite Element Method (FEM)-based commercial software under several lightning conditions, i.e., various basic lightning insulation levels (BIL) and different flashover mechanisms, taking into consideration still air and wind conditions for the voltage profile and its insulation strength analyses. The study found that the voltage profile condition for the proposed voltage uprating model was able to withstand its BIL under all conditions and thus satisfied the electrical requirement needed.